Student’s Perception on The Use of ICT to Improve Student’s Grammar in XII IPA 4 Class at SMA 20 Batam - Trisnauly Purba, Angelina; Richi San Triadi; Leil Badrah Zaki; Priambada Purba, Hilarius Raditya (English Education Study Program Faculty of Teacher Training and Education, 2024)
This study examines the perspective of 42 student’s of grade 12 and their teacher’s attitudes on ICT for grammar learning at SMA 20 Batam. Data was gathered through Likert- scale questionnaires and interviews. Initial observations reveal grammar skill deficiencies among students. Preliminary findings suggest students hold positive views on leveraging ICT tools like interactive platforms to strengthen problematic grammar areas. The researchers want to see if using things like mobile apps, game-based platforms like Quizizz, and other interactive platforms have a positive impact on developing stronger grammar proficiency. Pre- and post-assessments were conducted to evaluate the impact of implementing interactive platforms like Slido and Quizizz on improving grammar proficiency. Based on the pre- and post-questionnaires and interviews conducted, our study aims to address the following research questions:xDoes ICT can help to improving the student’s grammar proficiency? What are the student’s perception towards the use of ICT in learning grammar?. Moreover, the integration of platforms like Slido and Quizizz was found to contribute positively to grammar competence, understanding of the material, and overall class engagement. These findings support the potential of ICT in addressing grammar deficiencies and fostering a more dynamic and effective English language learning environment for high school students. Further research and consideration of widespread implementation may be warranted based on these encouraging results.